Georg Forster : German Cosmopolitan - Kontje, Todd (Max Kade Research Institute: Germans Beyond Europe, 2022)
Georg Forster (1754-1794) was famous during his lifetime, notorious after his death, and largely forgotten by the later nineteenth century. Remembered today as the young man who sailed around the world with Captain Cook and as one of the leading figures in the revolutionary Republic of Mainz, Forster was also a prolific writer and translator who left behind two travelogues, a series of essays on diverse topics, and numerous letters. This in-depth look at Forster's work and life reveals his importance for other writers of the age. Todd Kontje traces the major intellectual themes and challenges found in Forster's writings, interweaving close textual analysis with his rich but short life. Each chapter engages with themes that reflect the current debates in eighteenth-century literary and cultural studies, including changing notions of authorship, multilingualism, the representation of so-called primitive societies, Enlightenment ideas about race, and early forms of ecological thinking. As Kontje shows, Forster's peripatetic life, malleable sense of national identity, and fluency in multiple languages contrast with the image of the solitary genius in the "age of Goethe." In this way, Forster provides a different model of authorship and citizenship better understood in the context of an increasingly globalized world.Compellingly argued and engagingly written, this book restores Forster to his rightful place within the German literary tradition, and in so doing, it urges us to reconsider the age of Goethe as multilingual and malleable, local and cosmopolitan, dynamic and decentered. It will be welcomed by specialists in German studies and the Enlightenment.